Diet-related inflammation increases the odds of multiple sclerosis: Results from a large population-based prevalent case-control study in Jordan - Alhaj, Omar A.; Trabelsi, Khaled; Younes, Abdallah M.; Shivappa, Nitin; Bragazzi, Nicola L.; Hebert, James R.; Jahrami, Haitham A. (Frontiers in Nutrition, 2023)
Background: Multiple sclerosis, a chronic inflammatory disease in young and middle-aged adults, is one of the leading causes of non-traumatic disability in adults. Diet is known to have an important role in the modulating inflammatory processes and influencing molecular pathways. Purpose: This study aims to examine the association of the inflammatory capacity of diet measured by DII with MS in Jordan. Methods: This prevalent case-control study included participants of both sexes, aged between 20 and 60 years. The cases (n = 541) had a confirmed diagnosis of prevalent Multiple Sclerosis (MS) in the previous three years, and controls (n = 607) were apparently healthy individuals matched on sex and age (42 years). A validated Arabic food frequency questionnaire (FFQ) was utilized to obtain estimated dietary intake. Dietary data from the FFQ were analyzed using ESHA's Food Processor® nutrition analysis software, and the results were used to calculate the DII scores. Logistic regression analyses, controlling for covariates such as age, sex, body mass index, and smoking status, were used to measure the association between DII score and MS outcomes. Results: Cases consist a mixed sample of MS phenotypes and controls were comparable on age and sex. However, controls tended to be taller, lighter, had a lower BMI, and had a lower smoking rate. After controlling for age, BMI, sex, and smoking status, there was a consistent increase in MS risk according to DII score with a 10-fold increase in odds in quartile 4 vs. quartile 1 [ORquartile 4vs1 = 10.17 (95%CI: 6.88; 15.04)]. For each point increase in DII score, there was nearly a doubling odds [OR1 = 1.75 (95%CI: 1.59; 1.92)]. Individual nutrients and food values aligned according to their contribution to the DII score calculations. Conclusions: The findings obtained in MS patients with varied illness duration over the previous three years, are consistent with an association between the overall inflammatory potential of diet and MS odds. Our findings among MS participants showed a significantly more pro-inflammatory DII scores than age- and sex-matched controls. Our results also suggest that MS group had a diet rich in pro-inflammatory foods and nutrients.